(untitled) (Quinto Sol, 2011)
The paper presents the preliminary results of the study in course focused in the visual memories of Chaco Province immigration between the end of the 19th and the beginning of the 20th Century, taking in consideration their life histories registered in photography. The main purpose is to outline a social, historical and esthetical retrospective of Chaco photography practice, and to analyze through the photographic testimony, how immigrants view themselves and construct their own images and signification, from life celebrations – baptisms, weddings and birthdays – up to even the certification of death – funeral rituals. The work presents a first approach to a series of photographs taken between the 1880 and the 1950 decades in mostly Italian immigrant villages of the region. It considers a reflexive exercise based on the identification of common and reiterative elements within the heterogeneous photographic corpus of Chaco province immigration. Finally, the study analyzes the privileged representational models as the production and use conditions of photography.